Clinical manifestations and molecular aspects of phosphoribosylpyrophosphate synthetase superactivity in females. (21st March 2018) - Zikánová, Marie; Wahezi, Dawn; Hay, Arielle; Stibůrková, Blanka; Pitts, Charles; Mušálková, Dita; Škopová, Václava; Barešová, Veronika; Součková, Olga; Hodaňová, Kateřina; Živná, Martina; Stránecký, Viktor; et al.
Abstract: Objectives: Phosphoribosylpyrophosphate synthetase (PRPS1) superactivity is an X-linked disorder characterized by urate overproduction Online Mendelian Inheritance in Man (OMIM) gene reference 300661. This condition is thought to rarely affect women, and when it does, the clinical presentation is mild. We describe a 16-year-old African American female who developed progressive tophi, nephrolithiasis and acute kidney failure due to urate overproduction. Family history included a mother with tophaceous gout who developed end-stage kidney disease due to nephrolithiasis and an affected sister with polyarticular gout. The main aim of this study was to describe the clinical manifestations of PRPS1 superactivity in women. Methods: Whole exome sequencing was performed in affected females and their fathers. Results: Mutational analysis revealed a new c.520 G > A (p.G174R) mutation in the PRPS1 gene. The mutation resulted in decreased PRPS1 inhibition by ADP. Conclusion: Clinical findings in previously reported females with PRPS1 superactivity showed a high clinical penetrance of this disorder with a mean serum urate level of 8.5 (4.1) mg/dl [506 (247) μmol/l] and a high prevalence of gout. These findings indicate that all women in families with PRPS1 superactivity should be genetically screened for a mutation (for clinical management and genetic counselling). In addition, women with tophaceous gout, gout presenting in childhood, or a strong family history of severe gout should be considered for PRPS1 mutational analysis.